2006
DOI: 10.1007/s10551-005-5575-1
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Insurance Customer Dishonesty: Outline of a Moral-Sociological Approach

Abstract: Most consumer morality studies focus on consumer immorality, i.e. different types and degrees of consumer dishonesty or deviance. This paper follows this tradition, by looking at insurance customer dishonesty. For looking at insurance customer dishonesty in a wider perspective, the paper drafts a sociology of insurance customer morality, including outlines of micro-level, meso-level and macro-level moral sociologies of insurance fraud, as well as a discussion of moral heterogeneity and a critical understanding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 21 publications
2
25
0
Order By: Relevance
“…The area is included in a geographical region bearing high insurance rates with claims on policies reaching record levels during the past few years. This, and the fact that only current holders of homeowner's or renter's policies were included in the study (following suggestions by Brinkmann, 2005;Brinkmann and Lentz, 2006), ensured that the topic had particular relevance to those involved. Average age was 32.4 years (ranging from 22 to 68) with 43.5% female and 56.5% male.…”
Section: Samplementioning
confidence: 99%
See 1 more Smart Citation
“…The area is included in a geographical region bearing high insurance rates with claims on policies reaching record levels during the past few years. This, and the fact that only current holders of homeowner's or renter's policies were included in the study (following suggestions by Brinkmann, 2005;Brinkmann and Lentz, 2006), ensured that the topic had particular relevance to those involved. Average age was 32.4 years (ranging from 22 to 68) with 43.5% female and 56.5% male.…”
Section: Samplementioning
confidence: 99%
“…This belief likely contributes to consumer views that this particular type of fraudulent behavior is not unethical (cf. Brinkmann and Lentz, 2006). Indeed, industry reports indicate that between 25% and 35% of consumers view insurance claim padding as an acceptable practice (CAIF, 2003(CAIF, , 2007Smith, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Stiglitz (2009) pointed out that possible moral hazard could occur within this situation, that is, some customers may apply for the claims even if they know the losses are not covered by the policy (e.g., customers could make a claim by misreporting the loss event). Brinkmann and Lentz (2006) also pointed out that customers may try to obtain insurance money for a loss that is not covered by the policy. We think there are two possible reasons for customers claiming for non-covered losses.…”
Section: Jfc 213mentioning
confidence: 99%
“…Brinkmann and Lentz (2006) showed that the perception of premium unfairness and insurer's reputation had significant effects on customer acceptance of insurance customer dishonesty. Brinkmann and Lentz (2006) also argued that some customers are looking to get a fair return on the insurance premiums in the insurance claim frauds. Based on this finding, we think that fairness perceptions of loss-premium comparisons could affect customer acceptance of insurance claim frauds.…”
mentioning
confidence: 99%
“…In recent years, some commentators have viewed consumption as a medium through which to construct an ethical life in conditions of relative freedom (e.g. Douglas 1996) and/or relative risk (Al‐Rafee and Cronan 2006; Brinkmann and Lentz 2006; Steenhaut and Van Kenhove 2005). In this context, prominent current debates articulate questions of consumption and consumerism with questions of overseas development (Miller 2001), environmental sustainability (Crocker and Linden 1998; Wilk 2001) and obesity (Cafaro et al.…”
Section: Introductionmentioning
confidence: 99%